WOMEN’S ENDURING SILENT IN SHASHI DESHPANDE’S ‘THE BINDING VINE’, ‘THE DARK HOLDS NO TERRORS’ AND ‘ROOTS AND SHADOWS’ - Sekhar, V. (International Journal of Research -GRANTHAALAYAH, 2016)
The heroines of Shashi Deshpande’s novels has to pass through difficult situations all of her life. They have continued to get attacks of depression and dejection all through even when they are in the happiest moments of their life, they are not free from a fear of some misfortunes as they could see lurking in near future. As the novel “The Dark Holds No Terror” Shashi Deshpande records a deep impression upon Sarita’s psyche and also in the novel “ The Binding Vine“, the women characters are unhappy mostly due to their being superstitious conservation and reactionary. Then in” Roots and Shadows’, which describes how a woman dependent, insecure and gives her an incomplete sense of identity.